English Students’ Awareness Of American And British Variety Of English’s Differences - Agus Gunawan; Narti Aminah (Lingua, 2020)
English is the most used language in the world. Due to this reason, there are some variations are exist. For example are American and British variety of English. These varieties have some differences. It is very important for us to learn and know about its differences to make us easier in learning English. The purpose of this research is to find out the English students’ knowledge of American and British English. The Data were collected by two instruments, firstly is the tests about American and British variety of English differences in spelling and vocabulary and secondly is questionnaire about their usage and preferences of English varieties by using qualitative method. The participants in this study were 55 English students ​​at As-syafi’iyah Islamic University which have been learned about grammar, pronunciation, spelling and vocabulary course. Based on this research, it shows that students are already know about American and British English, but somehow they got some difficulties in distinguish The American and British English. But, they were able to answer all the tests although the result shows that not all their answers are correct. The research was concluded that the students used both English in American and English in British.